(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Dengue-COVID-19 overlap is mixture of both diseases sharing few similarities in pulmonary and extrapulmonary involvement. Due to high prevalence of both diseases later being pandemic disease, and overlapping laboratory and clinical parameters we have conducted a study to observe dengue-COVID-19 overlap in Indian settings in tertiary care hospitals. Methods: Prospective, observational study, included 600 COVID-19 cases with dengue NS1 or Dengue IgM positive, with lung involvement documented and categorized on HRCT thorax at entry point. All cases were subjected to dengue IgG antibody titers and dengue IgM/IgG antibody titer analysis after 12 weeks of discharge form hospital. Results: Dengue- COVID-19 overlap was documented in 16.33% (98/600) cases. CT severity has documented significant correlation with Dengue-COVID-19 overlap cases. [p<0.00001] Hematological evaluation, white blood cell count & platelet count were having significant association with Dengue-COVID-19 overlap [p<0.0076] & [p<0.00001] respectively. Clinical parameters as hypoxia have significant association with dengue- COVID-19 overlap. [p<0.00001] Inflammatory markers as IL-6, CRP and LDH has significant association in dengue-COVID-19overlap [p<0.00001] respectively. In study of 98 cases of ‘Dengue-COVID-19’, post covid lung fibrosis [p<0.004] and serological assessment in dengue IgM/IgG and covid antibody titers has significant association [p<0.00001] Conclusion: Dengue-COVID-19 overlap is clinical syndrome with overlapping clinical and laboratory workup of both the illnesses. High index of suspicion is must in all covid cases in tropical settings where dengue is endemic; and all cases with leucopenia and thrombocytopenia with fever should be screened for dengue serology. False positive dengue serology or dengue antigen crossreactivity is known to occur in underlying COVID-19 illness, and have impact on clinical outcome as it will result in delay in covid appropriate treatment initiation and many cases require intensive care unit treatment due to progressed covid pneumonia. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 189-199